Synchronisation of Flowering Periods Between Moghania macrophylla (Willd) O.Ktze and M. chappar Kuntze - Srivastava, S. C.; Kumar, P. (Indian Forester, 2003)
The difference in flowering periods of Moghania macrophylla and M. chappar is a serious constraint in hybridization between these two species. Synchronisation of flowering periods could be possible by delaying the flowering period of M. macrophylla through 3-4 times topping or pinching operations.